2020
DOI: 10.1007/s40137-020-00252-8
|View full text |Cite
|
Sign up to set email alerts
|

Educating the Public on Hemorrhage Control: Methods and Challenges of a Public Health Initiative

Abstract: Purpose of Review We aim to determine the various models of training and identify educational strategies that would be efficacious in teaching bleeding control to the public. Recent Findings Recent studies have examined various educational strategies of bleeding control education including lectures, web-based classes, and hands-on training. The effectiveness of these trainings can not only be measured in increases in knowledge, but also in feelings of confidence, preparedness, and willingness to assist in a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The majority of participants felt confident in their improved ability to control life-threatening hemorrhage both in and out of the hospital based on the “Until Help Arrives” Post-Course Survey [supplement attached].It has been shown that similar training methods are effective in teaching such life-saving skills, and may improve chances of survival for many patients that would not otherwise have immediate access to emergency care. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of participants felt confident in their improved ability to control life-threatening hemorrhage both in and out of the hospital based on the “Until Help Arrives” Post-Course Survey [supplement attached].It has been shown that similar training methods are effective in teaching such life-saving skills, and may improve chances of survival for many patients that would not otherwise have immediate access to emergency care. 6 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that similar training methods are effective in teaching such life-saving skills, and may improve chances of survival for many patients that would not otherwise have immediate access to emergency care. 6 Limitations of the study: It must be recognized that our method for assessing the effectiveness of this course was semi-quantitative and has not yet been shown to improve real-world outcomes. Further, the number of medically trained assessors was limited.…”
Section: Discussionmentioning
confidence: 99%